Numerical Modeling and Experimental Validation of Thermal Distribution in a Prototype Snakehead Fish (Channa striata) Extraction Chamber with Dual-Heater Configuration - Siregar, Izhary; Ahmad Jibril; Setyawan Dwi Nugroho; Agus Purwanto (Jurnal Inotera, 2026)
This study evaluates the thermal performance and extraction capacity of a developed steaming chamber utilizing a dual-heater configuration (2 x 200 W). A two-stage methodology was implemented: first, a numerical characterization using Computational Fluid Dynamics (CFD) to simulate convective heat distribution and fluid flow patterns; and second, an experimental validation using a physical prototype. The CFD results revealed a convection-dominated thermal field with a maximum wall temperature of 63.52°C and a center temperature of 55.22°C, maintaining a low thermal gradient of approximately 8.3°C. This uniformity ensured that fish samples remained at a stable exposure temperature of roughly 60°C during the initial heating phase. Experimental trials were conducted across a temperature range of 40–110°C and durations of 60–180 minutes. The results identified an optimal operating window between 80°C and 90°C for 120 minutes, yielding a peak extraction volume of 46.4 mL. Data trends indicated that while thermal energy is essential for liberating albumin from the tissue matrix, temperatures exceeding 100°C lead to a progressive decline in yield due to fluid evaporation and potential thermal degradation. Conversely, temperatures below 70°C proved insufficient for effective extraction. Qualitative chromatic analysis confirmed that the optimal 80–90°C range produced the most concentrated and opaque extracts.. The integration of CFD-based design and automated thermal control successfully demonstrates a robust framework for maximizing the recovery of thermosensitive fish essences in extraction chamber.